Lead contamination in human milk affects infants’ language trajectory: results from a prospective cohort study - Naspolini, Nathalia Ferrazzo; Vanzele, Pedro A. R.; Tótolo, Pedro; Schüroff, Paulo Alfonso; Fatori, Daniel; Vicentini Neto, Santos Alves; Barata-Silva, Cristiane; dos Santos, Lisia Maria Gobbo; Fujita, André; Passos-Bueno, Maria Rita; Beltrão-Braga, Patricia C. B.; Campos, Alline C.; et al. (Frontiers in Public Health, 2024)
Infants growing up in low- and middle-income countries are at increased risk of suffering adverse childhood experiences, including exposure to environmental pollution and lack of cognitive stimulation. In this study, we aimed to examine the levels of metals in the human milk of women living in São Paulo City, Brazil, and determine the effects on infants’ neurodevelopment. For such, a total of 185 human milk samples were analyzed for arsenic (As), lead (Pb), mercury (Hg), and cadmium (Cd) using inductively coupled plasma mass spectrometry (ICP-MS). We applied the Bayley scales of infant and toddler development Third Edition (Bayley-III) to assess developmental milestones. In our analysis, we found a mean (standard deviation) concentration of As in human milk equal to 2.76 (4.09) μg L−1, followed by Pb 2.09 (5.36) and Hg 1.96 (6.68). Cd was not detected. We observed that infants exposed to Pb presented language trajectories lower than non-exposed infants (β = −0.413; 95% CI -0.653, −0.173) after adjustment for infant age, maternal education, socioeconomic status, infant sex, and sample weights. Our results report As, Pb, and Hg contamination in human milk, and that infant exposure to Pb decreased infants’ language development. These results evidence maternal-child environmental exposure and its detrimental impact on infants’ health.